2005
DOI: 10.1095/biolreprod.104.035881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Follicle Size and Oocyte Maturation Conditions on Maternal Messenger RNA Regulation and Gene Expression in Rhesus Monkey Oocytes and Embryos1

Abstract: The relationship between alterations in gene expression and differences in developmental potential in primate oocytes and embryos was examined. Oocytes from 3 sources were used for these studies: 1) in vivo-matured oocytes from monkeys stimulated with FSH and hCG, 2) in vitro-matured oocytes from large follicles of monkeys primed with FSH, and 3) in vitro-matured oocytes from small follicles from nonstimulated (NS) monkeys. Following in vitro fertilization, embryos from these oocytes displayed high, moderate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 28 publications
4
29
1
1
Order By: Relevance
“…The results also imply functional alterations in steroid biosynthesis and metabolism, ion transport, cellular homeostasis, cell growth, stress response, and RNA binding and translation. Similar findings regarding upregulation of transcripts in IVM or incompetent oocytes have been reported in rhesus monkeys and humans (Zheng et al, 2005;Jones et al, 2008). It seems likely that both the oocyte and its supportive somatic cells are sensitive to the maturation environment and that a disruption of that environment can, by upsetting oocyte-somatic cell interactions, affect the transcriptional activity of the oocyte.…”
Section: Modulating Transcriptional Activity In the Oocyte Genomesupporting
confidence: 77%
“…The results also imply functional alterations in steroid biosynthesis and metabolism, ion transport, cellular homeostasis, cell growth, stress response, and RNA binding and translation. Similar findings regarding upregulation of transcripts in IVM or incompetent oocytes have been reported in rhesus monkeys and humans (Zheng et al, 2005;Jones et al, 2008). It seems likely that both the oocyte and its supportive somatic cells are sensitive to the maturation environment and that a disruption of that environment can, by upsetting oocyte-somatic cell interactions, affect the transcriptional activity of the oocyte.…”
Section: Modulating Transcriptional Activity In the Oocyte Genomesupporting
confidence: 77%
“…Oocytes matured in vitro from NS rhesus females display poor developmental competence (Zheng et al 2005) compared with 'in vivo-matured' oocytes. In vitro maturation of oocytes from FSH-primed females yields intermediate-quality oocytes (Schramm and Bavister 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed significant differences between mouse and human or non-human primate embryonic patterns of gene expression (Vassena et al 2005;Zheng et al 2005;Latham 2007, 2008), highlighting the value of a non-human primate model for detailed studies of developmental transitions and developmental mechanisms that may drive human embryogenesis. In addition, critical comparisons to understand the molecular basis of defective embryogenesis require the expenditure of high-quality oocytes and embryos for molecular analysis, which is precluded for the human by legal and ethical considerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the PREGER project (Zheng et al, 2004a(Zheng et al, , b, 2005a, more than 100 genes have been examined for their expression patterns in oocytes and preimplantation embryos have been assessed from three different sources: oocytes from non-stimulated small follicles, oocytes from FSH-stimulated large follicles, and oocytes from both FSH-and LH-stimulated follicles and matured in vivo. The first source of oocytes represents the population with least developmental competence, the third one represents oocytes with greatest developmental potential and the second represents those with intermediate potential.…”
Section: Effect Of Ivm On Overall Gene Expression Profiles In Rhesus mentioning
confidence: 99%